The effect of vitamin D consumption on pro-inflammatory cytokines in athletes: A systematic review of randomized controlled trials - Saedmocheshi, S.; Amiri, E.; Mehdipour, A.; Stefani, G. P. (Sports, 2024)
Vitamin D is essential for the optimal health of the skeletal system. However, this vitamin also plays a role in other functions of the human body, such as muscle, immune, and inflammatory functions. Some studies have reported that adequate levels of vitamin D improve immune system function by reducing the levels of certain pro-inflammatory cytokines, which can protect against the risk of post-exercise illness. This systematic review aims to investigate the effects of vitamin D supplementation on pro-inflammatory cytokines in athletes. This study was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A literature search was conducted in SPORTDiscus, PubMed, ScienceDirect, and Google Scholar up to 1 October 2023. The quality of the articles was evaluated using the Risk of Bias 2 Tool. After searching the databases, a total of 7417 studies were identified, 6 of which met the eligibility criteria, and their outcomes were presented. The six studies included 176 participants. All six studies are randomized control trials, including a total of 176 subjects, primarily men (81%). Regarding the types of athletes, most participants were endurance athletes. Our investigation in this systematic review demonstrated that out of the six studies, only two of them reported significant changes in IL-6 and TNF-a levels after taking high-dose vitamin D. Other studies did not present any significant changes after vitamin D supplementation in athletes with respect to IL-6 and TNF-a levels. Further studies are needed to determine the effectiveness of vitamin D supplementation for athletes as a disease-prone community.